MODEL PENINGKATAN KINERJA USAHA KECIL DAN MENENGAH MENGGUNAKAN THE DREAM HOUSE MODEL (Studi Kasus Industri Batik Tulis Lasem Kabupaten Rembang)* - Tahwin Muhammad; Kusumaningsih Novi (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
This research aims to formulate the performance enhancement model related with thecharacteristic of Batik Tulis Lasem industry. The data used is the primary data taken fromdistributed interviews and questionnaires to the entrepreneurs. Method and processing dataused is Ishikawa diagram, Importance Performance Analysis (IPA), The Dream House Model andForce Field Analysis. The research results: 1) Ishikawa Diagram Analysis shows that humanresources factor is the main cause of Batik Tulis Lasem industry problem. 2) Importanceperformance analysis (IPA) shows that there are three indicators of quadrant 1 and sevenindicators of quadrant III should be corrected and becomes the model pillar of performanceenhancement. 3) The dream house model as Batik Tulis Lasem performance enhancement modelhas four main pillars related with the organization management, productivites, product qualitiesand also marketing. 4) The main strategy in enhancing the performance of Batik Tulis Lasem isimproving of organization management, productivities, product qualities and integratedmarketing. The managerial implication as the research result is: 1) Giving training including fourmanagement aspects (management of human resources, production management, financesmanagement and marketing management); 2) The government facilities as the effort to developBatik Tulis Lasem industry.Key words: performance, Ishikawa Diagram, Importance Performance Analysis, The DreamHouse Model, and Force Field Analysis.